2021
DOI: 10.3390/microorganisms9051032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Bioprocessed Soybean Meal Ingredient on the Intestinal Microbiota of Hybrid Striped Bass, Morone chrysops x M. saxatilis

Abstract: The hybrid striped bass (Morone chrysops x M. saxatilis) is a carnivorous species and a major product of US aquaculture. To reduce costs and improve resource sustainability, traditional ingredients used in fish diets are becoming more broadly replaced by plant-based products; however, plant meals can be problematic for carnivorous fish. Bioprocessing has improved nutritional quality and allowed higher inclusions in fish diets, but these could potentially affect other systems such as the gut microbiome. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…For its part, W. confusa, which is also an antibacterial compound producer [76], has shown potential to positively impact fish growth performance, as well as stimulate the activity of some digestive enzymes [77]. Similarly, P. russelli has been associated with beneficial effects in terms of fish health and growth, especially regarding activities dealing with protein degradation [78], as elucidated in this paper.…”
Section: Gut Microbiome/fish Performance Correlationsmentioning
confidence: 71%
“…For its part, W. confusa, which is also an antibacterial compound producer [76], has shown potential to positively impact fish growth performance, as well as stimulate the activity of some digestive enzymes [77]. Similarly, P. russelli has been associated with beneficial effects in terms of fish health and growth, especially regarding activities dealing with protein degradation [78], as elucidated in this paper.…”
Section: Gut Microbiome/fish Performance Correlationsmentioning
confidence: 71%
“…Currently, foodborne intestinal inflammation is a major health and welfare issue in aquaculture. As fishmeal remains an important source of dietary protein in aquaculture diets, its increasing price and decreasing availability have given birth to a replacement of feed made from plant sources of dietary protein, such as soybean meal ( 1 ). The side effects resulting from plant-sourced proteins have occurred in many fish species, from carnivorous to herbivorous, such as salmon ( 2 ), grouper ( 3 ), zebrafish ( 4 , 5 ), and carp ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when fed several experimental dietary regimens, there were barely any modifications in the gut microbiota. On top of that, variations were observed in the bioprocessed soybean meal diet with different fractions in hybrid seabass (Fowler et al, 2021). In summary, while the generation of SCFAs is not the primary focus of this work, it is thought that adding soybeans alters the microbial makeup of fish guts, which may indirectly impact SCFA production.…”
Section: Soybean Mealmentioning
confidence: 93%
“…The inclusion of soybean meal is indirectly related to SCFA production due to the modification of the intestinal microbiota of fish. Interestingly, it has been observed that the experimental diets with bioprocessed soybean meal by Aureobasidium pllulans included three different fractions: bioprocessed soybean meal after enzymatic treatment, and additionally rinsed or washed bioprocessed soybean meal yielded diverse operational taxonomical unit (OTUs) in which Lactococcus lactis typically used for carbohydrate fermentation found to be abundant in the gut environment (Fowler et al, 2021). This resulted in more excellent gut interactions and enhanced growth, promoting metabolite production such as SCFAs in hybrid sea bass (Fowler et al, 2021).…”
Section: Soybean Mealmentioning
confidence: 99%